Investigating the interplay between personality, attachment, and high-risk behaviors in people living with HIV: A network analysis approach - Zadehparizi, Reza; Kianimoghadam, Amir Sam (Researcher Bulletin of Medical Sciences, 2025)
Objective: The prevalence of high-risk behaviors among individuals living with HIV remains a significant concern. Understanding the factors that contribute to these behaviors is crucial for developing effective interventions. This study aims to use network analysis to examine the complex relationships between personality traits, attachment styles, and high-risk behaviors in people with HIV, with the goal of identifying key factors and informing targeted interventions. Materials and Methods: Participants were recruited online, resulting in a sample of 452 individuals (68.1% male) with a mean age of 33.4 years. Measures included the PID-5-BF for personality traits, Self-reported Attachment Style for attachment styles, and RISQ for risky and impulsive behaviors. Results: The network analysis showed that among the study variables, PID 6 ("I'm not good at planning ahead") emerged as the most central node, exhibiting high values in betweenness centrality. Similarly, PID 7 ("My thoughts often don't make sense to others") displayed considerable centrality, highlighting its importance in shaping the overall network structure. Conclusion: These findings shed light on the complex relationships between personality, attachment, and high-risk behaviors in individuals with HIV. The identification of central nodes and strong edges provides valuable information for understanding the network structure and potential intervention targets